Efficiency of the anaerobic baffled reactor followed by anaerobic filter in the removal of nutrients and pathogenic organisms in fish processing effluents - Sousa, S. R. [UNESP]; Rodrigues, L. S.; Sampaio, R. R. [UNESP]; Dutra, J. C.F.; Silva, I. J. (FapUNIFESP (SciELO), 2022)
The aquaculture showed high growth along with the increase in the consumption of animal protein from this sector. The processing industries facilitate the preparation of fish for the consumer; however, they generate large volumes of effluents with a high polluting potential. Environmental legislation establishes norms for the release of effluents, making it necessary to implement treatment systems to reduce the pollutants generated. The objective of this work was to evaluate the performance of a compartmentalized anaerobic reactor (ABR) followed by an anaerobic filter (AF) treating fish processing effluent. The work was carried out in a slaughterhouse that had an effluent treatment station consisting of a static sieve, grease box, ABR reactor and anaerobic filter. Monitoring consisted of physical-chemical and biological analyzes of samples collected from the influent and effluents from each stage of treatment. The parameters evaluated were ammonia, nitrite, nitrate, NTK, phosphate and coliforms. The average results of the removal efficiency of these parameters, respectively, for the ABR reactor were 5, 40, 69, -19, -25 and 83%, and for the AF -0.5, 73, 53, 10, -17 and -17%. The system composed by the ABR reactor followed by the Anaerobic Filter showed high removal of nitrite, nitrate, and coliforms.
Eficiência do reator ABR seguido de filtro anaeróbio na remoção de nutrientes e de organismos patogênicos em efluentes de processamento de pescado
Keywords: Agroindustry; Anaerobic digestion; Environmental impact